Grisars beteende i bedövningsbox med luftskum eller kvävgasskum - Brattlund Hellgren, Rebecka (SLU/Dept. of Animal Environment and Health (until 231231), 2019)
The main stunning methods for commercial pig production in Europe are electricity and induced hypoxia with carbon dioxide. Although electrical stunning is considered good from an animal welfare point of view, it has its drawbacks due to necessity for individual handling prior to stunning as well as being less effective than carbon dioxide. Carbon dioxide has on the other hand been criticized for inducing pain and discomfort before stunning is completed. This study was conducted as part of a project with an overall aim to get the use of nitrogen foam approved according to the EU legislation for stunning of pigs at slaughter. The aim of the present study was to investigate the behavioral response of pigs exposed to air-filled and nitrogen-filled foam. Results showed that foam induces responses such as exploratory behavior towards the foam and stunning box roof as well as escape attempts towards the roof. Other behavioral responses did not show any relevant differences between air-filled foam and nitrogen-filled foam. However, the frequency of performed behaviors of pigs in nitrogen-filled foam declined right before loss of posture. In order to conclude that the method is less aversive than carbon dioxide more studies on pig behavior in this environment is necessary, as well as studies on how the foam is perceived when in contact with eyes and snout, or when introduced to a group of pigs. This may contribute to a better understanding of how effective nitrogen-filled foam is as a stunning agent, and in the long run aid the improvement of animal welfare at slaughter.